The Mistake in Carl Bosch’s PhD Thesis: A Contribution to ‘Retro-Chemistry’ - Smeilus, Toni; Hennig, Lothar; Beyer, Lothar; Sieler, Joachim; Giannis, Athanassios (Synthesis, 2015)
The reaction of diethyl 1,3-acetonedicarboxylate and 2-bromoacetophenone described in Carl Bosch’s PhD thesis revealed a mistake concerning the structure of the isolated compound. A rework of the original showed that not the described cyclohexenone derivative was isolated, but a highly functionalized α,β-unsaturated cyclopentenone derivative was formed. The structure was determined by spectroscopic methods and X-ray crystal structure analysis. In analogy to Bosch’s reaction, some new derivatives were synthesized.
Keywords: cyclization; condensation; amides; benzylation; esters